(3GSJNOGe GdCfJQfJ aj GdHMK GdYdej aj GdLRGFQ (B/s - (3YHOjT, UhfjIs ((3GdLRGFQ (B:s (3WGcSjL che ,s, 2015)
(3jSYi gPG GdcJGH Gdi JbOje GLhHI dHYV GdJSGDdGJ GdeJYdbI HhGbY GSJNOe GdGfJQfJ aj GdHMK GdYdej dOi GdHGMKjf GdLGeYjjf s
(3HjHdjhZQGajG(B:(3U(B.182- (3edGMXI (B: (3U(B.199-222s
Keywords: (3GdGfJQfGJs; (3GdCfJQfjJs; (3GdHMK GdYdejs; (3ehGbY GdCfJQfGJs